The Mindanao State University freshman high school students' ability to reason using proportion - Pattuinan, Dolores Saavedra 1948- (1979)
The Bourbaki group of Mathematicians viewed mathematics as the study of structures or systematic patterns of relationships. The researcher then considers proportionality a good starting point for an investigation in mathematics education. This study further sought to determine the relationships between the students' responses on the proportional reasoning tests their age, sex, mental ability, mathematics achievement and socio-economic status. The ratio test or Paper Clip Task and the Otis Quick-scoring Mental ability tests were used in the study. The responses of the subjects on the Ratio test were classified into 7 categories ranging from no answer to proportional reasoning. Relationships between the categorical responses on the ratio test and the subjects' age, sex, mental ability, mathematics achievement and socio-economic status.
"December, 1979."
Vita.
Thesis (M.A.T. Mathematics)--University of the Philippines, Diliman.
Keywords: Proportion -- Study and teaching (Secondary) -- Philippines -- Mindanao; High school freshmen -- Philippines -- Mindanao; Reasoning